Visualization of seismic vulnerability of buildings with the use of a mobile data transmission and an automated GIS-based tool. (April 2020) - Özsoy Özbay, Ayşe Elif; Sanrı Karapınar, Işıl; Ünen, Hüseyin Can
Abstract: This paper aims to introduce a computer-aided rapid visual screening framework and establish a prioritization strategy for seismic vulnerability evaluation of reinforced concrete buildings. A methodology is developed to organize and visualize the results of visual screening method with a GIS-oriented database system. Throughout the study, the primary rationale behind conducting the field data collection via utilization of spatial processes is to achieve a standardized and efficient data flow in the presence of multiple data collectors on the field, working in coordination. Incorporated in the process are mobile data collection tools with cloud-support, open online spatial databases, and open-source GIS software. The utilization of these tools instead of paper forms would lead to readily available standardized responses via digital forms, avoiding loss and fragmentation of data and ambiguities in classification, where multiple users contribute to the same repository. In addition, the use of digital tools in field data collection eliminates the data transcription process, significantly reducing the time required for it. Hence, the proposed framework has the potential to represent a fast and reliable overview of structural seismic vulnerability as well as seismic priority for strengthening. As a result of this study, the mobile data transmission in the field and the visualization in GIS are highly recommended to be a standard part of the seismic evaluation procedure.